Annual Report 2000 - Partnerships put to the test [2] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Special Paper in CTA Annual Report 2000 by Patrick A Antoine discusses Global economic change and the relevance of information and communication management for stakeholders in rural development, with special reference to the Caribbean region.